2015
DOI: 10.7150/jca.13107
|View full text |Cite
|
Sign up to set email alerts
|

CD20 Over-Expression in Hodgkin-Reed-Sternberg Cells of Classical Hodgkin Lymphoma: the Neglected Quest

Abstract: We have scrutinized a previously analyzed cohort of classical Hodgkin lymphoma patients for evidence of a CD20 over-expression. This was pursued in order to determine whether all the 24 (12.6%) CD20+++ patients had clinical and/or biological profiles which would warrant a separate consideration and treatment or would carry a different outcome from our 166 CD20 (-) classical Hodgkin lymphoma patients. Except for an older age and a significantly lower expression of non-sialyl-CD15 antigen, both previously descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In fact, the prognostic relevance of BCA, p53, and Bcl2 in cHL is highly controversial. Literature data on BCA are focused mainly on CD20 and correlate its expression to either worse, 40 neutral, 41,42 or better 43 survival rates compared with controls. The same holds true for Bcl2 and p53, which have been variably associated with prognosis 10,20,43‐49 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the prognostic relevance of BCA, p53, and Bcl2 in cHL is highly controversial. Literature data on BCA are focused mainly on CD20 and correlate its expression to either worse, 40 neutral, 41,42 or better 43 survival rates compared with controls. The same holds true for Bcl2 and p53, which have been variably associated with prognosis 10,20,43‐49 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, older patients were reported to have a higher proportion of CD20-positivity than younger patients. 18 , 26 - 29 As our study found no significant correlation between CD79a and CD20 expression, they may be independent B-cell markers in CHL. Indeed, CD20- and CD79a-positivity were reported to be only weakly correlated.…”
Section: Discussionmentioning
confidence: 46%
“…In contrast to CD79a, the prognostic impact of CD20 has been well documented, although controversies remain. 26 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation, stage, clinical course, and response to therapy do not differ from conventional CD20-negative cases. 41,42 In equivocal cases, additional pan-B-cell markers (CD19, CD79a, BOB.1, and OCT-2), which are negative in CHL and positive in non-Hodgkin lymphomas, are necessary. Another source of potential confusion includes primary mediastinal B-cell lymphoma and nonmediastinal "gray-zone lymphoma," which in biopsy specimens demonstrate overlap between CHL and DLBCL, with foci resembling one or the other entity or with areas that show overlapping histologic features of both.…”
Section: Presence Of Rare Large Pleomorphic Cellsmentioning
confidence: 99%